2014
DOI: 10.11564/28-0-556
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diarrhea among young children under the age of five in Kenya, evidence from KDHS 2008-09

Abstract: [AOR, 0.796; 95% CI, and residence of mother [AOR, 0.538; 95% CI, [AOR, 0,796, IC 95%, de 0,559 à 1,134] et résidence de la mère [AOR, 0,538, IC à 95% de 0,324 à 0,895] sont plus susceptibles d'influencer la diarrhée infantile. Niveau de l'enseignement supérieur de la mère a été associée à une plus faible incidence de la diarrhée infantile [AOR, 0,187, IC à 95% de 0,609 à 0,573]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
8
11
0
2
Order By: Relevance
“…Our study also showed that the risk of developing diarrhoea in children whose households use protected water sources was 68% lower compared to their counterparts who use unprotected water sources. This finding is similar with a study by [24] in Kenya who found that sources of drinking water was one of the household characteristics that had significant influence on childhood diarrhoea. However, a study conducted in southwest Ethiopia by [25] did not find any significant association of diarrhoeal occurrence and drinking water sources.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also showed that the risk of developing diarrhoea in children whose households use protected water sources was 68% lower compared to their counterparts who use unprotected water sources. This finding is similar with a study by [24] in Kenya who found that sources of drinking water was one of the household characteristics that had significant influence on childhood diarrhoea. However, a study conducted in southwest Ethiopia by [25] did not find any significant association of diarrhoeal occurrence and drinking water sources.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also showed that the risk of developing diarrhoea in children whose households use protected water sources was 68% lower chance compared to their counterparts who use unprotected water sources. This finding is similar with a study by [24] in Kenya who found that sources of drinking water was one of the households' characteristics that had significant influence on childhood diarrhoea. However, a study conducted in southwest Ethiopia by [25] did not find any significant association of diarrhoeal occurrence and drinking water sources.…”
Section: Discussionsupporting
confidence: 90%
“…Children born after 24-35, 36-47, and more than 47 months of the preceding birth intervals had a lower risk of child mortality relative to children born less than 24 months. This finding was consistent with a study conducted in Ethiopia (20), Kenya (21) and India (22). This could be shorter birth intervals are associated with maternal nutritional reduction and the child would prone to malnutrition and then end up with death.…”
Section: Analysis Of Multilevel Negative Binomial Regression Modelsupporting
confidence: 92%